DEVELOPMENT OF A MONTE CARLO SIMULATION TOOL FOR LIGHT TRANSPORT INSIDE SCINTILLATION CRYSTALS - Yang, Xin (My University, 2012)
The scintillation crystal is a critical component in positron emission tomography (PET) systems. It impacts a number of PET system performance parameters, including spatial, energy, and time resolution. Our goal is to develop a new simulation tool to achieve improved accuracy by addressing several limitations in the existing packages, including more advanced surface treatments, temporal dependency of photon arrival, and rigorous experimental validations. The comparison of preliminary Monte Carlo simulation results and analytical calculations for specular reflection suggest that the simulation model is working well. The time-resolved light output was studied for various crystal surface treatment configurations. The measured energy resolutions are in the range of approximately 10% to 15%, which are in good agreement with published literatures. Based on the simulation and experimental results, the polished surface treatment, used together with an external specular reflector, is able to provide the best energy resolution and timing resolution for a LYSO (3x3x20 mm3) and SiPM assembly we tested. The AsCut surface with external diffusion reflector is not desired due to its inferior energy and timing resolutions. The direction and recommendation of improvements of simulation regarding surface models and wavelength dependency, as well as potential optimization of experiment such as timing pickoff methods, are discussed.
Keywords: positron emission tomography; Monte Carlo simulation; Scintillation Crystals; Optics; Medical Biophysics; Medical Biophysics